KEGIATAN SALES CALL DALAM PENJUALAN KAMAR DI GRAND HOTEL LEMBANG - Januar Aprilukito; Violetta Simatupang; Maksum Suparman (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2017)
In the business process of hospitality, sales and marketing has a very crucial role because it is a benchmark in obtaining revenue. This study aims to examine (1) the approach phase of sales call activity in the sale of Grand Hotel Lembang room; (2) the stage of sales call presentation in Grand Hotel Lembang room sales ?; (3) the complaints adjudication stage and the sales call activity in Grand Hotel Lembang's room sales, and (4) the closing stages of sales call activities in Grand Hotel Lembang's room sales. This research uses descriptive research method. This research was conducted at Grand Hotel Lembang, Bandung. The results showed that (1) the ability of Sales People to be in approach stage in sales call activity in Grand Hotel Lembang sales; (2) the ability of sales people can not be said to either approach with prospective customers or categorized in enough categories; (3) the ability of sales people at presentation stage in sales call activity in selling room; (4) the stage of sales call activity in the sale of Grand Hotel Lembang room into the category of enough; (5) Sales People capability in the complaints adjudication stage and inquiries on sales call activities in Grand Hotel Lembang room sales, and; (6) Sales People ability at closing stage in sales call activity in Grand Hotel Lembang room sales. into the category enough.